An insight into non-emissive excited states in conjugated polymers - Hu, Zhongjian (Nat Commun, 2015)
Conjugated polymers in the solid state usually exhibit low fluorescence quantum yields, which limit their applications in many areas such as light-emitting diodes. Despite considerable research efforts, the underlying mechanism still remains controversial and elusive. Here, the nature and properties of excited states in the archetypal polythiophene are investigated via aggregates suspended in solvents with different dielectric constants (ɛ). In relatively polar solvents (ɛ>∼ 3), the aggregates exhibit a low fluorescence quantum yield (QY) of 2–5%, similar to bulk films, however, in relatively nonpolar solvents (ɛ<∼ 3) they demonstrate much higher fluorescence QY up to 20–30%. A series of mixed quantum-classical atomistic simulations illustrate that dielectric induced stabilization of nonradiative charge-transfer (CT) type states can lead to similar drastic reduction in fluorescence QY as seen experimentally. Fluorescence lifetime measurement reveals that the CT-type states exist as a competitive channel of the formation of emissive exciton-type states.